Botanical characterization, phytochemistry, biosynthesis, pharmacology clinical application, and breeding techniques of the Chinese herbal medicine Fritillaria unibracteata - Zhang, Yamei; Han, Hongping; Li, Dingai; Fan, Yanan; Liu, Meng; Ren, Huimin; Liu, Lu (Frontiers in Pharmacology, 2024)
Fritillaria unibracteata (FRU) belongs to the genus Fritillaria of the Liliaceae family. It is one of the original plants of the Chinese medicinal material "Chuanbeimu" and also a biological resource featured in the Tibetan Plateau of China. The dried bulbs of FRU are used in traditional Chinese medicine. The chemical constituents of FRU that have been isolated and identified include alkaloids, sterols, organic acids and their esters, nucleosides and volatile oils. FRU has antitussive, expectorant, anti-asthmatic, anti-inflammatory, antibacterial, acute lung injury-reducing, antifibrosis, antitumor, and other pharmacological effects. This valuable plant has an extremely high market demand, and over the years, due to over-exploitation, FRU has now been listed as a key species that is endangered and scarcely cultivated in China as a traditional Chinese medicinal herb. However, research on FRU is rare, and its effective components, resource control, and mechanisms of action need further study. This review systematically discusses the herbal characteristics, resource distribution, chemical composition, biosynthesis, pharmacological effects, clinical application, and breeding techniques of FRU, hoping to provide a reference for further research and the use of FRU.